Chapter 16 Ageism and Dementia (2018)
This chapter explores the relationship between ageism and dementia. Although dementia is not an unavoidable consequence of ageing, increasing age is the biggest risk factor for having this disease. The prevalence of dementia increases exponentially with age and 95% of those with Alzheimer’s Disease, the most common form of dementia, are aged 65 or over. Dementia often has strong negative connotations, partly driven by alarmist media portrayals of the disease, which means that people living with the condition can experience the ‘double stigma’ of ageism and dementia-related discrimination. The stigma attached to dementia can have significant implications for quality of life through, for example, decreased social engagement, reduced self-esteem, increased carer burden and sub-standard healthcare, a situation that is exacerbated by low levels of diagnosis and inadequate training of medical professionals. Despite attempts by governments and not for profit organisations to tackle dementia-related stigma, there remains a strong need to raise awareness of the realities of living with dementia and to reduce the impact of discrimination. This chapter explores the inter-connections and overlaps between ageing and discrimination because someone has dementia. The relationship between dementia and age is discussed, followed by an exploration of the impacts of dementia-related stigma for the individual and society. The chapter continues by analysing the role of the media in fuelling stigma and how having dementia can impact on the receipt of health and social care services. The chapter explores the implications of dementia stigma for social engagement and ends by considering how perceptions of dementia are reflected in research funding.